Dose-response relationship between urinary polycyclic aromatic hydrocarbons metabolites and urinary 8-hydroxy-2′-deoxyguanosine in a Chinese general population - Sun, Huizhen; Hou, Jian; Zhou, Yun; Yang, Yuqing; Cheng, Juan; Xu, Tian; Xiao, Lili; Chen, Weihong; Yuan, Jing (Chemosphere (Oxford), 2017)
Association of exposure to polycyclic aromatic hydrocarbons (PAHs) with increased urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) formation has been reported in occupational population and children. However, studies on the association between them in general population are limited. A total of 1864 eligible subjects from the baseline Wuhan participants of the Wuhan-Zhuhai Cohort Study (n = 3053) were included in this study, after excluding individuals with certain disease and missing data on urinary monohydroxy PAHs (OH-PAHs) and 8-OHdG levels. Urinary monohydroxy PAHs and 8-OHdG levels were measured by gas chromatography-mass spectrometry and high performance liquid chromatography-electrochemical detection, respectively. Association of urinary OH-PAHs with urinary 8-OHdG was analyzed by multiple linear regression analysis. We found a dose-dependent relationship between urinary PAHs metabolites and urinary 8-OHdG (p < 0.05 for all). Furthermore, more evidence for the association of total concentrations of urinary OH-PAHs with 8-OHdG levels were observed in individuals with normal body mass index or central obesity (p < 0.01 for all). There was a dose-dependent relationship between urinary OH-PAHs levels and urinary 8-OHdG levels among a general Chinese population. Exposure to background PAHs may have a greater influence on urinary 8-OHdG levels in individuals with central obesity. [Display omitted] •Urinary OH-PAHs were associated with a dose-dependent increase in urinary 8-OHdG.•Urinary OH-PAHs had stronger association with urinary 8-OHdG in nonobese adults.•Urinary 8-OHdG was prominently affected by PAH exposure in central obesity adults.